2022
DOI: 10.3390/molecules27217593
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzable Tannins in the Management of Th1, Th2 and Th17 Inflammatory-Related Diseases

Abstract: Plants rich in hydrolyzable tannins were traditionally used all over the world for a variety of chronic inflammatory disorders, including arthritis, colitis, and dermatitis. However, the knowledge of their immunological targets is still limited though fundamental for their rational use in phytotherapy. The recent advances regarding the pathogenesis of inflammatory-based diseases represent an opportunity to elucidate the pharmacological mechanism of plant-derived metabolites with immunomodulatory activity. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…The impact of ellagitannins on the Rho GTPase pathway is still poorly described, although other sources of ellagitannins have been investigated for their anti-inflammatory and antitumoral effect at the gut level [ 48 ]. Regarding inflammation, we could not exclude, on the basis of the literature concerning ellagitannins [ 16 ], that post-transcriptional and enzymatic mechanisms may have contributed to IL-8 inhibition in our setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of ellagitannins on the Rho GTPase pathway is still poorly described, although other sources of ellagitannins have been investigated for their anti-inflammatory and antitumoral effect at the gut level [ 48 ]. Regarding inflammation, we could not exclude, on the basis of the literature concerning ellagitannins [ 16 ], that post-transcriptional and enzymatic mechanisms may have contributed to IL-8 inhibition in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ellagitannins in dietary products, such as fruits from Punica granatum L. and Rubus spp., contributes to their preclinical efficacy against gastric ulcer [ 12 , 13 , 14 , 15 ]. The antioxidant and anti-inflammatory properties of ellagitannins, observed through different experimental models [ 16 , 17 ], are supposed to contribute to the gastroprotective effect. Moreover, Funatogawa and colleagues suggested that ellagitannins also inhibit the growth of clinical strains of H. pylori at μM concentrations in microbiological tests [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two subtypes are integral in regulating proin ammatory and anti-in ammatory factors, playing pivotal roles in the immune response. Normally, the early in ammatory response is dominated by Th1, followed by an enhanced Th2 response to prevent the damage caused by excessive Th1 activity [37]. However, an imbalance between the two immune responses may lead to persistent in ammation, hindering wound healing [38].…”
Section: Expression Of Key Genes In Single Cellsmentioning
confidence: 99%
“…Th1/Th2 imbalance is the main immunological mechanism of AD disease. The obvious imbalance of Th2 cells leads to increased levels of type 2 cytokines, among which IL-4 and IL-13 can cause initial tissue inflammation, IgE synthesis, mast cell (MC) activation, and basophil and eosinophil (EOS) aggregation [5], and their combination with the proinflammatory factor TNF-α can induce an AD-like phenotype in human skin tissue equivalents. It is characterized by spongiform changes in the epidermis, changes in the differentiation of keratinocytes (KC) and changes in the lipid composition of the stratum corneum [6].…”
Section: Th2 Cellsmentioning
confidence: 99%